2021
DOI: 10.1007/s10096-020-04127-9
|View full text |Cite
|
Sign up to set email alerts
|

Variations in respiratory pathogen carriage among a homeless population in a shelter for men in Marseille, France, March–July 2020: cross-sectional 1-day surveys

Abstract: We aimed to compare respiratory pathogen carriage by PCR during three different time periods in 2020 in sheltered homeless people in Marseille, France. The overall prevalence of respiratory pathogen carriage in late March–early April (69.9%) was significantly higher than in late April (42.3%) and mid-July (45.1%). Bacterial carriage significantly decreased between late March–early April and late April. SARS-CoV-2 was detected only in late March–early April samples (20.6%). Measures aiming at mitigating SARS-Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(35 citation statements)
references
References 15 publications
0
35
0
Order By: Relevance
“…A number of included studies reported infection attack rates of SARS-CoV-2 among study participants: 29 studies measured positivity rates (i.e., current infection) [ 13 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ], seven measured seroprevalence (i.e., prevalence of antibodies for SARS-CoV-2, indicating historic infection) [ 61 , 62 , 63 , 64 , 65 , 66 , 67 ], and four measured both positivity and seroprevalence rates [ 68 , 69 , 70 , 71 ]. Additionally, data regarding SARS-CoV-2 symptoms reported by study participants were provided by 32 articles [ 7 , 8 , 33 , 34 , 35 , 36 , 38 , 42 , 45 , 46 , …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of included studies reported infection attack rates of SARS-CoV-2 among study participants: 29 studies measured positivity rates (i.e., current infection) [ 13 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ], seven measured seroprevalence (i.e., prevalence of antibodies for SARS-CoV-2, indicating historic infection) [ 61 , 62 , 63 , 64 , 65 , 66 , 67 ], and four measured both positivity and seroprevalence rates [ 68 , 69 , 70 , 71 ]. Additionally, data regarding SARS-CoV-2 symptoms reported by study participants were provided by 32 articles [ 7 , 8 , 33 , 34 , 35 , 36 , 38 , 42 , 45 , 46 , …”
Section: Resultsmentioning
confidence: 99%
“…Among studies that measured positivity rates, 13 included testing of participants in response to an outbreak [ 34 , 36 , 38 , 39 , 40 , 43 , 44 , 45 , 48 , 50 , 55 , 56 , 68 ]. In addition, surveillance testing (i.e., testing not prompted by a confirmed or suspected outbreak) was conducted for all participants regardless of symptoms in 16 studies [ 33 , 35 , 36 , 38 , 40 , 41 , 42 , 43 , 44 , 46 , 47 , 52 , 58 , 69 , 70 , 71 ]. Of these, six reported that routine surveillance testing occurred regularly [ 35 , 41 , 44 , 52 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…19 quantitative studies were conducted in the USA [23À41], three in Canada [42À44],three in France [16,45,46], two in Italy [47,48], and one in Belgium [49], Spain [50], Slovakia [51], and Denmark [52], respectively. The data collection period considering all studies ranged from January 2020 to October 2020.…”
Section: Resultsmentioning
confidence: 99%